ANALISIS KEPUASAN PENGUNJUNG WEBSITE UNIVERSITASDENGAN PENDEKATAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) (Study Kasus: UNIKA Widya Mandala Madiun) - Setiyo Waloyo, L. Anang (Widya Warta, 2018)
Website is a good medium for effective promotion; sending and receiving information can be done very quickly. Correct and accurate information will have an impact on society, namely increasing public trust. Quality analysis of website usage was applied to measure the level of user satisfaction with the information and services needed. This study analyzed the amount of users’ satisfaction with university websites using the Importance Performance Analysis (IPA) approach. The recommendation of the IPA results is to prioritize maintaining the quality of information and services.